2008
DOI: 10.1017/s0022149x07873627
|View full text |Cite
|
Sign up to set email alerts
|

In vitronematicidal effects of medicinal plants from the Sierra de Huautla, Biosphere Reserve, Morelos, Mexico againstHaemonchus contortusinfective larvae

Abstract: Twenty extracts from plants from Sierra de Huautla Biosphere Reserve, Morelos, Mexico were evaluated against Haemonchus contortus infective larvae in an in vitro assay. The plant species evaluated were Bursera copallifera, B. grandifolia, Lippia graveolens, Passiflora mexicana, Prosopis laevigata, Randia echinocarpa and Urtica dioica. The plants were separated into their parts and macerated with different solvents (n-hexane, acetone, ethanol and methanol). An in vitro assay was used to evaluate the anthelminti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Several studies have been conducted in various parts of the world, including India, depicting the anthelmintic activity of herbal extracts against H. contortus (Melo et al, 2003; Tandon et al, 2004; Roy et al, 2008a, b; Buske et al, 2013). Evaluation of anthelmintic activity is based on the in vitro egg hatch assay, larval development inhibition (Hordegen et al, 2006; Costa et al, 2008; Maphosa et al, 2010; Ademola & Eloff, 2011; Gregory et al, 2015) and a few studies on adulticidal assays (Barrau et al, 2005; López-Aroche et al, 2008; Akkari et al, 2014). In vitro studies are considered to be pilot screenings of herbal extracts, also assumed to be effective in in vivo trials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted in various parts of the world, including India, depicting the anthelmintic activity of herbal extracts against H. contortus (Melo et al, 2003; Tandon et al, 2004; Roy et al, 2008a, b; Buske et al, 2013). Evaluation of anthelmintic activity is based on the in vitro egg hatch assay, larval development inhibition (Hordegen et al, 2006; Costa et al, 2008; Maphosa et al, 2010; Ademola & Eloff, 2011; Gregory et al, 2015) and a few studies on adulticidal assays (Barrau et al, 2005; López-Aroche et al, 2008; Akkari et al, 2014). In vitro studies are considered to be pilot screenings of herbal extracts, also assumed to be effective in in vivo trials.…”
Section: Introductionmentioning
confidence: 99%
“…Some P. laevigata plant extracts have being used as home remedies to cure a number of mouth and eye infections (Monroy-Ortiz & Castillo, 2007); however, so far, there is no information about their possible in vivo nematocidal effect. In a recent work published by López-Aroche et al (2008), an assay was performed to evaluate the in vitro nematocidal activity of a number of different plant extracts obtained from the Sierra de Huautla, an ecological reserve situated in the Morelos state, Mexico. They recorded 50 and 85% nematocidal activity with P. laevigata n -hexane extract against H. contortus infective larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a couple of research studies were conducted to evaluate the in vitro nematocidal effect of several plant extracts from La Sierra de Huautla ecological reserve, within the boundaries of the Morelos State in Mexico, including P. laevigata against infective larvae (L3) and fourth-stage larvae of the sheep abomasum nematode Haemonchus contortus . The results showed that the lethal activity against this parasitic nematode was 86 and 82.4% for L 3 and L 4 stages, respectively (Galicia-Aguilar et al , 2008; López-Aroche et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In in vitro studies, other investigations reported a lesser effect (20–40 mg/mL) on H. contortus larval mortality, including the hexane extract from the aerial parts of Prosopis laevigata , an acetone extract from the stem of B. copallifera [96], a hydro-methanolic extract from Larrea tridentata and aqueous extracts from Cydista aequinoctialis , Heliotropium indicum , and Momordica charantia (Table 22) [97,98].…”
Section: Nematicidal Compounds and Plant Extractsmentioning
confidence: 99%